The Narrative of Support and Opposition Among Social Media Users Towards Polygamy Content: An Exegetical Analysis of QS. An-Nisā' Verse 3 - Widia Usada; Muhammad Zikri (Fakultas Syariah dan Hukum Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyse the meaning and law of polygamy from the perspective of the Qur'an, based on the interpretation of QS. An-Nisa verse 3. The issues examined in this study concern how the concept of polygamy is understood in Islam and how the principle of justice is applied in practice in accordance with sharia guidance. This study uses a qualitative method with a library research approach and a thematic tafsir method, with the main sources being the Qur'an and various classical and contemporary tafsir works such as Tafsir Al-Maraghi, Tafsir Al-Manar, Tafsir Al-Mishbah, and Tafsir Ibn Kathir. The results of the study show that QS. An-Nisa verse 3 does not encourage polygamy, but merely permits it under certain conditions, with the main requirement being the ability to act justly, both physically and spiritually. The discussion shows that polygamy in Islam is a form of concession aimed at safeguarding social and moral welfare, not at satisfying carnal desire. In conclusion, polygamy in Islam is permitted to a limited extent, accompanied by a great responsibility to uphold justice and avoid harm, in accordance with the principle of maqāṣid al-sharī'ah.